The Role of NGOs in Combating Poverty in Developing Countries: A Comparative Study & Lessons Learned - Naguib, Menna Allah Mohamed; Afandy, Attia Hussien; ELbagoury, Ayman Amin (The Arab Journal of Administration, 2025)
The significance of the current study stems from the fact that it analyses the theoretical determinants of the nexus between Non-Governmental Organizations (NGOs) and the fight against poverty. It also examines those determinants within the framework of some international experiences, namely Bangladesh, Tunisia and Brazil. The study has compared the role of NGOs in combating poverty and has analysed the strengths and weaknesses in the work of these Organizations in the experiences under study in order to benefit from them in developing countries. The study has adopted the comparative approach. It concluded that NGOs were distinctive in one of the dimensions of combating poverty in the cases of the study, and that the performance of these Organizations in the Bangladesh experiences is better than its counterparts in Tunisia and Brazil. The study also classified the lessons learned from these experiences into a group of legal, Political, institutional and human determinants to benefit from them in developing countries.